Supporting materials for teaching process safety. Issue 2 (24th April 2013) - Louvar, Joseph F.
<x xml:space="preserve">Abstract</x> This article contains supporting materials and information that can be added to any safety course to improve the effectiveness of teaching in a university course or in an industrial seminar. These materials are primarily selected from a huge source of available materials by Safety and Chemical Engineering Education Committee (SAChE) and the U.S. Chemical Safety Board. The selection process is based on my own industrial and teaching experiences: (a) materials that I know emphasized the industrially important safety concepts and (b) materials and information that give the students and young professionals a positive safety culture; that is, the long lasting interest, knowledge, and motivation to prevent process accidents and injuries. The concepts described and stressed in this article include (a) motivation or reasons for studying process safety, (b) laboratory safety (including requirements for wearing safety glasses), (c) reactive chemicals, (d) boiling liquid expanding vapor explosions (BLEVEs), (e) hazards of dusts, (f) confined space entry, (g) nitrogen asphyxiation, (h) safety reviews and introduction to PSM, (i) Piper Alpha and details of PSM, and (j) continuing education. This article also identifies the source of existing and readily available process safety course lecture materials: the core materials that are enhanced with the supporting materials and information described in this article. © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013